Short-Term Evaluation of Left Ventricular Mass and Function in Children With Growth Hormone Deficiency After Replacement Treatment - Gómez-Guzmán, E.; Cañete, M. D.; Valle-Martos, R.; Cañete, R.; Valle, M.; Jiménez-Reina, L.; Caballero-Villarraso, J. (Frontiers in Pediatrics, 2018)
Background: Our study was designed to assess the effects of GHD on nutritional and metabolic parameters, brain natriuretic peptide (BNP) levels, and left ventricular mass (LVM) in prepubertal children and after short-term GH replacement therapy. Materials and Methods: This prospective study enrolled 81 children. We compared 40 GHD children (16 males and 24 females) to 41 healthy children (control group) (18 males and 23 females). All subjects were at Tanner Stage I (aged 7-11 years). At the baseline, a blood sample was drawn and echocardiographic images were obtained. These tests were repeated on the GHD subjects after 6 months of GH replacement therapy. Body surface, weight, size, blood pressure, heart rate, glucose, insulin, HOMA-IR, HOMA-β, QUICKI, cholesterol, HDLc, LDLc, triglycerides, IGF1 and IGFBP3 were measured. Indexed LVM, diastolic and systolic diameter (dD-sD), diastolic and systolic LV function, isovolumic relaxation time, right ventricle function and BNP levels were obtained through echocardiography. These parameters were correlated to growth factors. Data were analyzed using Student’s t-test or U-Mann-Whitney-test and Pearson’s correlation, considering p<0.05 to be significant. Results: Indexed LVM was smaller in GHD patients than in controls, whereas diastolic and systolic functions, BNP, metabolic, and nutritional profiles were similar. After treatment, nutritional and metabolic profiles significantly improved, though diastolic and systolic functions did not seem to have changed. There was a significant increase in LVM. Indexed LVM was similar to that of controls. Significant correlations were obtained between LVM-IGF1 and sD-IGFBP3. Conclusions: GHD in childhood is associated with a lower indexed LVM. In the short-term, GH increases the indexed LVM, while maintaining normal systolic and diastolic functions, BNP, and an improved lipid profile.